Bioconversion of glycerol into polyhydroxyalkanoates by a salt-tolerant indigenous strain, Halomonas titanicae KHS3 - Escobar, Mariana (2018)
Halomonas titanicae KHS3 was isolated from hydrocarbon-contaminated water in Mar del Plata harbor. This strain is able to accumulate polyhydroxyalkanoates (PHAs), reserve polymers that can be used as raw material for the preparation of bioplastics.The aim of this work was to evaluate the ability of H. titanicae KHS3 to use glycerol as the only source of carbon and energy and convert it into PHAs.When grown in mineral salts medium with 0.25% commercial glycerol, PHAs synthesis was only moderate. However, when cells were harvested at mid-exponential phase and resuspended in medium depleted of nitrogen source, PHA accumulation was dramatically increased and reached up to 70% of dry cell weight. Such accumulation also occurred when cultures were fed with glycerol obtained from a biodiesel reactor, both in its crude form (contaminated with methanol and salts) and partially purified (technical grade), suggesting that this bioconversion potentially represents a way of adding value to the otherwise disposable glycerol.We show the kinetics of PHA accumulation after nitrogen deprivation under different conditions. Good PHA accumulation occurred in media containing between 2 and 10% NaCl. PHAs inside cells remained stable after long incubations in nitrogen-lacking medium, but decreased rapidly after re-addition of ammonium sulfate.The purified polymer is currently analyzed by RMN to determine its precise chemical composition.